SISTEM MONITORING KONDISI PASIEN KARANTINA COVID-19 BERBASIS INTERNET OF THINGS - Mohamad Jamil (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Self-quarantine is recommended for patients who are positive for Corona but do not show symptoms or the symptoms are very minimal. Generally, these patients are young under 60 years old without any complications. There are several things to do while undergoing quarantine. Any person in quarantine who has a fever or respiratory symptoms, at any time during the quarantine period, must be treated and managed as a suspected COVID-19 case. Implement standard precautions for all quarantined persons and quarantine officers (family members). The purpose of this study is to design a Monitoring System for the condition of Covid-19 quarantine patients based on the Internet of Things. Based on the results of the tests carried out, data in the form of temperature measurement results, spo2, and BPM of quarantine patients can be obtained which are displayed on a web-based application.